2005
DOI: 10.1007/s10147-005-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-small-cell lung cancer: reirradiation for loco-regional relapse previously treated with radiation therapy

Abstract: Reirradiation is considered to contribute to salvage in selected patients with relapsed non-small-cell lung cancer. Patients with a long interval after the initial irradiation are good candidates for reirradiation. On the other hand, patients with Eastern Cooperative Oncology Group (ECOG) performance status 3 were not good candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 15 publications
2
47
2
Order By: Relevance
“…Tada et al [5] reported that the OS rates for 19 patients who were re-irradiated with conformal radiotherapy were 26 and 11% for years 1 and 2, respectively. A comparison of our SBRT result with published data by Wu et al [4] who used 3DCRT shows that a better local control rate can be obtained with SBRT with a 1-year rate of 69% compared to 51%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tada et al [5] reported that the OS rates for 19 patients who were re-irradiated with conformal radiotherapy were 26 and 11% for years 1 and 2, respectively. A comparison of our SBRT result with published data by Wu et al [4] who used 3DCRT shows that a better local control rate can be obtained with SBRT with a 1-year rate of 69% compared to 51%.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with locoregional relapse or second cancers in the thoracic region after definitive radiotherapy are generally not suitable for surgery and the response rates to second-line chemotherapy are low without the provision of durable control [3], re-irradiation remains as a treatment option using limited radiation doses which can be tolerated by the surrounding previously irradiated critical tissues. Palliative or definitive re-irradiation of locally recurrent or persistent NSCLC using conventional radiotherapy has been explored by multiple groups reporting variable success with 2-year locoregional control rates of only 42% at a median dose of 51 Gy [4][5][6]. In their review, Jeremic et al [7] summarized that conventional external beam radiotherapy (EBRT) for re-irradiation of recurrent lung cancer yields suboptimal local control rates of 50-60% and a 3-5% risk of grade 3 or higher toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Re-irradiation with conventional radiation has been reported as well with variable success. [5][6][7][8][9] Stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (SRT) have become routine treatment options for patients with brain metastases. [10][11][12][13][14][15] High fractional dose is more effective for radiation resistant cells.…”
Section: Introductionmentioning
confidence: 99%
“…The real impact of time intervals needs to be studied in better established prospective protocols and cannot be answered in the framework of this case study. Tada, et al [6] reported on the feasibility of repeated irradiations using longer time intervals.…”
Section: Discussionmentioning
confidence: 99%